Conducting Embodied Research at the Intersection of Performance Studies, Experimental Ethnography and Indigenous Methodologies - Magnat, Virginie (Anthropologica, 2022)
Grounding embodied research in Indigenous method- ologies as well as feminist, sensory and experimental ethnog- raphy, I propose an alternative performance-based approach modelled on the creative work of women from different cultures and generations who collaborated with influential theatre inno- vator Jerzy Grotowski. I infer from my experimental fieldwork and embodied research on the work of these artists that posi- tionality, relationality, relevance, respect, and reciprocity are critical to articulating experiential ways of cognition beyond the limitations imposed by dominant conceptions of knowledge. Having foregrounded the Indigenous and environmentalist cri- tique of performance-based methodologies derived from the work of Augusto Boal and Paulo Freire, I suggest that alterna- tive approaches which allow for the interrelation of creativity, agency, embodiment and spirituality can help promote more diverse and inclusive perspectives.